2020
DOI: 10.1096/fasebj.2020.34.s1.02005
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of a biflavone as a novel inhibitor of TRPV4‐dependent proatherogenic processes in macrophages

Abstract: Atherosclerosis, a chronic inflammatory disease, is the major cause of mortality and morbidity in the United States. Studies suggest that arterial stiffness is a marker and a risk factor for atherosclerosis. Recent reports from our laboratory showed that TRPV4 (transient receptor potential channel of the vanilloid subfamily 4), a mechanosensitive ion channel, plays a role in oxidized LDL (oxLDL)‐induced macrophage foam cell formation, a critical process in atherogenesis. We performed a high‐throughput screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It may also be useful for the treatment of cardiovascular disease. Cell-based studies showed its potential as an inhibitor of TRPV4-mediated proatherogenic processes in macrophages [ 50 ]. In addition, ginkgetin showed inhibitory effects on human thrombin, an important serine protease that regulates the blood coagulation cascade and processes of thrombosis [ 51 ], and pancreatic lipase, an important target that regulates lipid uptake [ 52 ].…”
Section: Ginkgetinmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be useful for the treatment of cardiovascular disease. Cell-based studies showed its potential as an inhibitor of TRPV4-mediated proatherogenic processes in macrophages [ 50 ]. In addition, ginkgetin showed inhibitory effects on human thrombin, an important serine protease that regulates the blood coagulation cascade and processes of thrombosis [ 51 ], and pancreatic lipase, an important target that regulates lipid uptake [ 52 ].…”
Section: Ginkgetinmentioning
confidence: 99%
“…Flavonoids are widely recognized as a molecule with good antioxidant activity and beneficial effects in the treatment of neurological disorders [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Ginkgetin For the Treatment Of Neurodegenerative Diseasesmentioning
confidence: 99%